Towards The Reduction of The National Impact of Blindness Due to Glaucoma- A National Glaucoma Summit - Dr. Barbie O. M. Ejukonemu (Journal of Medical Biomedical and Applied Sciences, 2020)
Glaucoma is a serious condition that involves elevation in pressure inside the eye caused by build-up of excess fluid. Though there are several varieties of the disease that do not show elevation of pressure inside the eyes, generally, glaucoma in whatever form, if left untreated would lead to impairment in vision by causing irreversible damage to the optic nerve and eventually blindness. Between 2005 and 2007 the National Programme for the Prevention of Blindness (NPPB), now known as National Eye Care Programme, in collaboration with states, local government and FCT embarked on National Blindness and low vision survey. The survey revealed that glaucoma, an unavoidable cause of blindness constitutes 16% of all blindness in the country. There are global initiatives that work to eradicate blindness in National communities in the developed and developing world. The major one being the Vision 2020 - the right to sight. Nigeria endorsed the initiative. This initiative is complacent on glaucoma as it is unavoidable, incurable and not within the targeted disease conditions of vision 2020. Elimination of blindness due to glaucoma in our communities, therefore calls for a National action. This paper is an advocacy for a National Summit on Glaucoma that would produce a National Glaucoma Eradication document; implementation of which would lead to reduction and elimination of the National impact of blindness due to glaucoma.